NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL DIKTA DAN HUKUM SERTA RELEVANSINYA DENGAN PENDIDIKAN AGAMA ISLAM - Hasna Abiyyu; Rifqi Muntaqo; Mukromin (SPESIFIK: Jurnal Pendidikan dan Pembelajaran, 2026)
This study examines the values of character education in Dhia'an Farah's novel "Dikta Dan Hukum" and its relevance to Islamic religious education. This study, a qualitative literature study, aims to determine the values of character education contained in Dhia'an Farah's novel "Dikta dan Hukum" and their relevance to Islamic religious education teachings.The results indicate that the implied and explicitly stated characters in the novel are closely aligned with character education values, making them relevant for integration into Islamic religious education materials and providing a concrete depiction of behavior reflecting good character in everyday life. The relevance of Dhia'an Farah's novel "Dikta dan Hukum" emphasizes the value of character education, especially in everyday life. Through the depiction of characters who reflect moral and spiritual values, the novel serves not only as entertainment but also as a guideline for fostering noble character in society. The characters in the story demonstrate how character education can guide individuals to face life's challenges with integrity and faith.